Imam Khameini: Filsafat Politik Islam, Vilayat-e Faqih, dan Demokrasi Sejati - Idris Thaha (Refleksi: Jurnal Kajian Agama dan Filsafat, 2003)
This paper explores the political thought of Imam Khamenei, focusing on Islamic political philosophy, the concept of Vilayat-e Faqih, and its relationship to true democracy. Imam Khamenei, as the leader of the Iranian Islamic Revolution and a staunch proponent of Vilayat-e Faqih, offers profound insights into political governance based on Islamic teachings. The paper will first explain Imam Khamenei’s Islamic political philosophy, emphasizing principles of justice, Sharia-based leadership, and the central role of scholars in governance. It will then discuss the concept of Vilayat-e Faqih, the principle of clerical leadership with authority to govern society based on Islamic law. Vilayat-e Faqih is a crucial foundation of the Iranian political system and central to Imam Khamenei’s thought. Next, the paper will explore the relationship between Vilayat-e Faqih and true democracy from Imam Khamenei’s perspective. Although it appears different from Western democratic concepts, Imam Khamenei argues that the Islamic political system implemented through Vilayat-e Faqih can embody the principles of true democracy by emphasizing popular participation and the enforcement of justice. Through a thorough analysis of Imam Khamenei’s political thought, this paper aims to provide a comprehensive understanding of how Islamic political philosophy, the concept of Vilayat-e Faqih, and the principles of true democracy interact and influence one another within the framework of contemporary politics.